PROSES PEMINDANGAN IKAN LAYANG (Decapterus sp) DI DESA JANGKAR KABUPATEN SITUBONDO. - Ika Junianingsih (Faculty of Science and Technology University Ibrahimy, 2015)
The purpose of this research is to know the traditional treatment processes, prinsi principles fish processing boiled and boiled fish economic value. The method used in this study is observation, interview and participation. These results indicate that the boiled fish processing are as follows. 1) Receipt of raw materials, 2) storage, 3) sorting, 4) washing, 5) the restructuring and salting, 6) preparation, 7) boiling, 8) cooling, 9) transportation, 10) marketing. Principles of boiled fish processing are as follows. 1) washing the fish, 2) the preparation of fish, 3) the preparation of container, 4) salting fish, 5) boiling fish. The economic value of the business pemindangan fish is as follows. profit of Rp. 437 160 000 / year, the value of ratio R / C amounting to 1,448% and the ROI of 14.48. In the process the fish pemindangan expected to improve sanitation and hygiene, especially in environmental sanitation. At the time of the washing process needs to be repeated washings so that the product really awake quality. Regarding the profits earned by the business unit pemindangan this flying fish, should continue to improve the quality of the fish being processed, so that profits continued to increase from year to year.